PHK Secara Sepihak Terhadap Karyawan Pabrik Ban Goodyear Bogor Ditinjau dari UU Ketenagakerjaan - Hibatullah, Abdurrafi; Tambunan, Daniel; Hadhani, Muhammad Gading Bintang; Rasyad, Pasha Athallah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Employment law in Indonesia is very important to ensure that citizens can obtain jobs as well as recognized rights and obligations. The employment relationship resembles a binding agreement between the employer and the worker, in which there are balanced rights and responsibilities. This is regulated by various parties, including employers, the government, wage boards, and labor unions. However, there are problems in the labor sector in Indonesia, one of which is unilateral termination of employment (PHK) by companies. One example of unilateral termination of employment in Indonesia is the case of the unilateral dismissal of 44 employees at the Goodyear tire factory. The author uses a normative juridical method. Primary legal sources are taken from Law No. 13 of 2003 concerning Manpower, while secondary legal sources are obtained through a review of legal literature related to labor, journals, and the internet. This study aims to understand labor issues in Indonesia, namely unilateral termination of employment by companies. The results of the study indicate that the implementation of termination by the company towards the employees of the Goodyear tire factory should comply with Law No. 13 of 2003 concerning Manpower. The company must also be responsible to the employees by paying severity pay, service appreciation money, and compensation for rights that should be received.